(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A set S of vertices in G = (V, E) is called a dominating set of G if every vertex not in S has at least one neighbour in S. A dominating set S of a graph G is said to be a certified dominating set of G if every vertex in S has either zero or at least two neighbours in